Cholinergic innervation of principal neurons in the cochlear nucleus of the Mongolian gerbil. Issue 10 (1st April 2018) - Gillet, Charlène; Goyer, David; Kurth, Stefanie; Griebel, Hannah; Kuenzel, Thomas
Abstract: Principal neurons in the ventral cochlear nucleus (VCN) receive powerful ascending excitation and pass on the auditory information with exquisite temporal fidelity. Despite being dominated by ascending inputs, the VCN also receives descending cholinergic connections from olivocochlear neurons and from higher regions in the pontomesencephalic tegmentum. In Mongolian gerbils, acetylcholine acts as an excitatory and modulatory neurotransmitter on VCN neurons, but the anatomical structure of cholinergic innervation of gerbil VCN is not well described. We applied fluorescent immunohistochemical staining to elucidate the development and the cellular localization of presynaptic and postsynaptic components of the cholinergic system in the VCN of the Mongolian gerbil. We found that cholinergic fibers (stained with antibodies against the vesicular acetylcholine transporter) were present before hearing onset at P5, but innervation density increased in animals after P10. Early in development cholinergic fibers invaded the VCN from the medial side, spread along the perimeter and finally innervated all parts of the nucleus only after the onset of hearing. Cholinergic fibers ran in a rostro‐caudal direction within the nucleus and formed en‐passant swellings in the neuropil between principal neurons. Nicotinic and muscarinic receptors were expressed differentially in the VCN, with nicotinic receptors being mostly expressed in dendritic areas while muscarinic receptors were located predominantly in somatic membranes. These anatomical data support physiological indications that cholinergic innervation plays a role in modulating information processing in the cochlear nucleus. Abstract : Using fluorescent staining techniques, the authors show that cholinergic axons innervate mainly dendritic areas of time‐coding neurons in the cochlear nucleus of hearing Mongolian gerbils. This study elucidates the anatomical basis of descending modulatory connectivity of a lower sensory brain area.